Contemporary Chinese creatives as literati - Liboriussen, Bjarke; Joaquin, Lopez-Mugica; White, Andrew (Routledge, 2018)
The importation of the creative industries 1 policy and discourse in China in the early twenty-first century has both reinforced the government’s desire to encourage more innovation and amplified existing tensions over differing conceptions of creativity. Along with China’s entry into the World Trade Organization (WTO) in 2001, the adoption of policies to develop the creative industries has bolstered the nation’s rapid modernization program. Producers of creative content in China have found themselves having to navigate difficult domestic and international policy domains, where restrictions on content and pressure to project a certain image of China at home have been complicated by a need to produce content which appeals to highly commercial global markets. As this chapter will demonstrate, attempts to resolve this tension have engendered a creative industries policy approach significantly different not only from other continents, but from the rest of Asia too. It is against this background we conducted interviews to explore how and why some of today’s Chinese artists choose to identify themselves as ‘literati’. The literati’s ‘purist’ view of art opens up a space for critical reflection, from the perspective of the Chinese creative producer, on China’s integration into global creative industries discourse and policy making.